Advances in nutraceutical applications in cancer : recent research trends and clinical applications - Gupta, Sheeba Varghese; Pathak, Yashwant (Boca Raton : CRC Press, 2018)
"This book provides a comprehensive view of historic, current, and technological advances of nutraceuticals' applications in cancer. In case of cancer, it describes how nutraceuticals act as a preventive agent and integrative therapy with the main stream anticancer therapy"--
OCLC-licensed vendor bibliographic record.
Keywords: Cancer -- Diet therapy; Functional foods -- Therapeutic use; Cancer -- Prevention; MEDICAL / Oncology; SCIENCE / Chemistry / General; TECHNOLOGY / Food Science